The Modernization Potential of Gas Turbines in the Coal-Fired Power Industry Thermal and Economic Effectiveness - Bartnik, Ryszard (SpringerBriefs in Applied Sciences and Technology, 2013)
The opportunity of repowering the existing condensing power stations by means of  gas turbogenerators offers an important opportunity to considerably improvement of their energy efficiency. The Modernization Potential of Gas turbines in the Coal-Fired Power Industry presents the methodology, calculation procedures and tools used to support enterprise planning for adapting power stations to dual-fuel gas-steam combined-cycle technologies. Both the conceptual and practical aspects of the conversion of existing coal-fired power plants is covered. Discussions of the feasibility, advantages and disadvantages and possible methods are supported by chapters presenting equations of energy efficiency for the conditions of repowering a power unit by installing a gas turbogenerator in a parallel system and the results of technical calculations involving the selection heating structures of heat recovery steam generators. A methodology for analyzing thermodynamic and economic effectiveness for the selection of a structure of the heat recovery steam generator for the repowered power unit is also explained. The Modernization Potential of Gas turbines in the Coal-Fired Power Industry is an informative monograph written for researchers, postgraduate students and policy makers in power engineering.